Entrepreneurial Culture as an Entry Point for Sustainable Growth in Egypt - Al-Makhzangy, Amany (The Arab Journal of Administration, 2022)
amanis@oi.edu.eg Entrepreneurship is a spark to achieve economic prosperity, as it helps increase job creation, which reduces unemployment, the creation of new methods of management and work, the introduction of innovative products and services, and support for innovation activities that have become the key to modern theories of development and growth, and one of the most important keys to competitiveness and business success, As competition in the global economy has become based on knowledge and innovation, all of the above makes entrepreneurship an engine of economic growth. Therefore, the Innovation and Entrepreneurship Unit of the Global Practices Sector for Trade and Competition builds the capabilities of promising companies in High-growth sectors such as agricultural activities, information and communications technology, and clean technology. A global network of business incubation centers has been established in various fields to support young entrepreneurs at every step of their journey by financing the initial stages, providing technical training and market information, and the study confirmed a joint integration relationship between the Entrepreneurship Index (GEI) and development The sustainable dimension with its various dimensions, the developmental dimension and the social dimension, where the study results resulted in a high correlation coefficient R2 99.5%, 99.3%, respectively, at the level of significance of 1%. And reduce its carbon emissions R2 27.3% were using analysis (ARDL) Auto -Regressive Distributed Lag Model.